DESIGN OF TEACHING MATERIALS FOR ELECTROLYTE AND NON-ELECTROLYTE SOLUTIONS TO SUPPORT THE IMPLEMENTATION OF NON-ROUTINE STRATEGY LEARNING FOR PRE-SERVICE CHEMISTRY TEACHER STUDENTS - Mujakir (SPIN JURNAL KIMIA & PENDIDIKAN KIMIA, 2025)
This study aims to design teaching materials that can optimize the implementation of non-routine learning strategies in the classroom. Non-routine learning focuses on the development of critical, creative, and adaptive thinking skills, so flexible, contextual devices are needed that can encourage active participation of students. The research method used is Research and Development (R&D) with an iterative design approach. The teaching materials that were designed were then validated by three experts, revised based on input, and limited trials in the classroom. The results of the study showed that non-routine-based teaching materials to support the implementation of non-routine learning strategies were very significant. The average difference in the increase in the abilities of UIN Sultan Syarif Kasim Riau students was 7.83 and UIN Ar-Raniry Banda Aceh was 7.9. Therefore, it is recommended to continue to develop and expand the use of this non-routine learning strategy in other universities to improve the quality of education in chemistry.